Factores de riesgos psicosociales en trabajadores de producción de una empresa textil en la ciudad de Lima - Paredes Tarazona, Mildred Teresa (2025)
This descriptive research examines the psychosocial risk factors affecting workers in a textile company located in Lima, Peru. A stratified random sample of 265 production workers, including those in the Spinning, Weaving, and Dyeing Areas, was selected for analysis. The research employed the SUSESO/ISTAS 21 Questionnaire, an adapted version of the Copenhagen Psychosocial Questionnaire (COPSOQ), tailored explicitly for collective application in Lima. The findings revealed a high percentage of psychosocial risks among the workers: psychological demands (45.28%), active work and development opportunities (55.09%), social support and leadership quality (75.09%), compensation (55.47%), and double presence (84.52%). Chi-square tests showed a significant relationship between psychosocial risk factors and sociodemographic variables, with an asymptotic significance (two-tailed) of 0.05. Notably, the Weaving Area exhibited the highest levels of psychosocial risks among the population studied.